Role of Modified Atmosphere in Pest Control and Mechanism of Its Effect on Insects - Cao, Yu; Xu, Kangkang; Zhu, Xiaoye; Bai, Yu; Yang, Wenjia; Li, Can (Frontiers in Physiology, 2019)
Pests not only attack field crops during the growing season, but also damage grains and other food products stored in granaries. Modified or controlled atmospheres (MAs or CAs) with higher or lower concentrations of atmospheric gases, mainly oxygen (O2), carbon dioxide (CO2), ozone (O3), and nitric oxide (NO), provide a cost-effective method to kill target pests and protect stored products. In this review, the most recent discoveries in the field of MAs are discussed, with a focus on pest control as well as current MA technologies. Although MAs have been used for more than 30 years in pest control and play a role in storage pest management, the specific mechanisms by which insects are affected by and adapt to low O2 (hypoxia) and high carbon CO2 (hypercapnia) are not completely understood. Insect tolerance to hypoxia/anoxia and hypercapnia involves a decrease in aerobic metabolism, including decreased NADPH enzyme activity, and subsequently, decreases in glutathione production and catalase, superoxide dismutase, glutathione-S-transferase and glutathione peroxidase activities, as well as increases in carboxyl esterase and phosphatase activities. In addition, hypoxia induces energy and nutrient production, and in adapted insects, glycolysis and pyruvate carboxylase fluxes are downregulated, accompanied with O2 consumption and acetate production. Consequently, genes encoding various signal transduction pathway components, including epidermal growth factor, insulin, Notch, and Toll/Imd signaling, are downregulated. We review the changes in insect energy and nutrient sources, metabolic enzymes, and molecular pathways in response to modified O2, CO2, NO, and O3 concentrations, as well as the role of MAs in pest control. This knowledge will be useful for applying MAs in combination with temperature control for pest control in stored food products.